Strong decline in female sterilization rates in Norway after the introduction of a new copayment system: a registry based study - Schøyen Unni; Skjeldestad Finn E; Bakken Inger J; Husby Marit G (BMC, 2007)
Abstract Background January 1, 2002, copayment for outpatient female sterilization in Norwegian public hospitals increased from 33 euros to 750 euros after a revision of the health care system. The aim of the present study was to investigate the effect of the new copayment system on female sterilization epidemiology. Methods We retrieved data on all female sterilizations 1999-2005 (N = 23 1333) from the Norwegian Patient Register, an administrative register to which it is mandatory for all hospitals to report. Sterilizations with diagnostic codes indicative of vaginal delivery, caesarean section, spontaneous abortion, ectopic pregnancy, and termination of pregnancy were analyzed separately. All other sterilizations were defined as "interval sterilization". Results An abrupt fall in female sterilization was observed after the raise in copayment. Age-adjusted incidence rates dropped from 6.3-6.8 per 1000 women in 1999-2001 to 2.2-2.3 per 1000 women during 2002-2005. Interval sterilizations dropped to 25% of the previous level after the rise in copayment while sterilizations in conjunction with caesarean section and postpartum sterilization remained constant. Conclusion For many Norwegian women seeking contraception, sterilization is no longer an available alternative.